Small RNAs as Fundamental Players in the Transference of Information During Bacterial Infectious Diseases - González Plaza, Juan José (Frontiers in Molecular Biosciences, 2020)
Communication shapes life on Earth. Transference of information has played a paramount role on the evolution of all living or extinct organisms since the appearance of life. Success or failure in this process will determine the prevalence or disappearance of a certain set of genes, the basis of Darwinian paradigm. Among different molecules used for transmission or reception of information, RNA plays a key role. For instance, the early precursors of life were information molecules based in primitive RNA forms. A growing field of research has focused on the contribution of small non-coding RNA forms due to its role on infectious diseases. These are short RNA species that carry out regulatory tasks in cis or trans. Small RNAs have shown their relevance in fine tuning the expression and activity of important regulators of essential genes for bacteria. Regulation of targets occurs through a plethora of mechanisms, including mRNA stabilization/destabilization, driving target mRNAs to degradation, or direct binding to regulatory proteins. Different studies have been conducted during the interplay of pathogenic bacteria with several hosts, including humans, animals, or plants. The sRNAs help the invader to quickly adapt to the change in environmental conditions when it enters in the host, or passes to a free state. The adaptation is achieved by direct targeting of the pathogen genes, or subversion of the host immune system. Pathogens trigger also an immune response in the host, which has been shown as well to be regulated by a wide range of sRNAs. This review focuses on the most recent host-pathogen interaction studies during bacterial infectious diseases, providing both the perspective of the host and the pathogen.